Bharat Ka Samvidhan: Samvidhan ke ek sau chatvain sansodhan, 2023 sahit sabhi sansodhanio ko samavesh karte hue - Ambedkar, Bhimrao (New Delhi Jain Book Agency, 2024)
This special A4 sized book in HINDI is a true collector's prized possession, now fully coloured. This unique book - a beautiful state-of-the art production is bigger than any other in the market. It is marvelously printed on superior art paper throughout. It contains * full text of the Constitution of India, 1950 as amended by The Constitution (106th amendment) Act, 2023 and Abolition of Article 370 * Original pictures/images/illustrations inserted in the original book in 1950 (like Ram Darbar, Shri Krishna narrating Geeta, Lord Mahaveer, Gautam Buddha, etc.) * detachable coloured "Original Preamble of 1950" and "Current Preamble" for your personal framing * many rare photographs and press coverings during 1948-1950 * original Speech of Dr. Rajendra Prasad while accepting the final draft of Dr. Ambedkar's Constitution in November 1949 * An Introduction to the Indian Constitution * Copy of the Original Signatures of the Constituent Committee * Alphabetical Index, and many more unique features. The cover is specially designed with foam padding. The gold-gilding on all side edges makes it worth preserving as a collectible book!
Keywords: Law; Constitution- India; Constitution- India- Including all 106 Amendments